2021
DOI: 10.1093/biosci/biab018
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Top-Down and Bottom-Up Approaches in Environmental Observing

Abstract: Effective responses to rapid environmental change rely on observations to inform planning and decision-making. Reviewing literature from 124 programs across the globe and analyzing survey data for 30 Arctic community-based monitoring programs, we compare top-down, large-scale program driven approaches with bottom-up approaches initiated and steered at the community level. Connecting these two approaches and linking to Indigenous and local knowledge yields benefits including improved information products and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 70 publications
1
44
0
2
Order By: Relevance
“…Nationally funded "top-down" research commonly only engages local communities after a proposal has been written and funded whereas "Bottom-up" community-based projects may have limited connections to large-scale scientific studies being conducted in proximity to these communities. Eicken et al (2021), put forth recommendations for bridging the "top-down" and "bottom-up" divide that lie at the heart of the ICON science. These include coordinating the priorities and methodology in observing and data management programs at appropriate scales.…”
Section: Challenges To Icon and Jedi Work In Epspmentioning
confidence: 99%
“…Nationally funded "top-down" research commonly only engages local communities after a proposal has been written and funded whereas "Bottom-up" community-based projects may have limited connections to large-scale scientific studies being conducted in proximity to these communities. Eicken et al (2021), put forth recommendations for bridging the "top-down" and "bottom-up" divide that lie at the heart of the ICON science. These include coordinating the priorities and methodology in observing and data management programs at appropriate scales.…”
Section: Challenges To Icon and Jedi Work In Epspmentioning
confidence: 99%
“…There remain significant challenges in bridging knowledge systems and providing opportunities and resources, although the needle is starting to move. In addition to community-driven observing initiatives and individual collaborations at the local scale [44,45], there is encouragement in SAON ROADS calling for Indigenous-led Expert Panels to help identify and prioritize observations with societal benefits in mind [41]. As another example, Canada and the United Kingdom recently agreed to cooperatively fund the Canada-Inuit Nunangat-United Kingdom Arctic Research Program, which is guided by the National Inuit Strategy on Research [46] and requires full Inuit engagement in leadership, design, development and execution.…”
Section: Monitoring Arctic Changementioning
confidence: 99%
“…Although, many questions remain as to how to best steward and manage such reserves. Different assessments have demonstrated that Indigenous, community-based management and support activities, such as community-driven monitoring, are most effective in ensuring adaptive and sustainable resource management in rapidly changing environments [45,53]. In the Arctic, increasing devolution of regulatory powers to the local, typically Indigenousmanaged scale is evident.…”
Section: Supporting Adaptation To the Changing Arcticmentioning
confidence: 99%
“…In contrast with Indigenous knowledge, local knowledge does not presuppose a broader, shared worldview, although it often is associated with a shared local understanding of context. Most local and Indigenous knowledge systems are empirically tested, applied, contested, and validated through different means in different contexts (Hill et al, 2020;Eicken et al, 2021). These specific guiding principles in SAON's strategic plan aim to support equity in addition to rigor, as fragmented science efforts that do not engage these principles can lead to false conclusions (e.g., Ward-Fear et al, 2019;Raymond et al, 2020).…”
Section: Introductionmentioning
confidence: 99%